Does emotional exhaustion influence turnover intention among early-career employees? A moderated-mediation study on Malaysian SMEs - Tajneen Affnaan Saleh; Abdullah Sarwar; Nasreen Khan; Mosab I. Tabash; Mohammad Imtiaz Hossain (Cogent Business & Management, 2023)
The aim of the present study was to investigate the relationship between early-career employees' emotional exhaustion and turnover intention in the information technology sector. Given the scarce empirical evidence on how turnover intention and emotional exhaustion can be reduced among early-career employees, ethical leadership was investigated as a mediator in this relationship based on the Social Exchange Theory (SET). Furthermore, using the Conservation of Resource Theory (COR), this study sought to understand the moderating role of a specific organizational ethical climate (i.e. self-interest climate) in the relationships among emotional exhaustion, ethical leadership, and turnover intention. Data was collected using convenience sampling from 243 early-career employees working in small and medium enterprises in the information technology sector. The results of structural equation modeling (SEM) indicated that early-career employees' emotional exhaustion significantly increases their turnover intention. This effect was found to be mediated by low ethical leadership and moderated by the self-interest ethical climate. However, the findings did not support the moderating effect of the self-interest ethical climate on the relationship between ethical leadership and employees' turnover intention. This study contributes to the existing knowledge on COR and SET by incorporating the antecedents of turnover intention, which have a significant impact on employees' decision-making regarding withdrawal. Additionally, the study addresses the underexplored topic of specific ethical climates and their effects on employees. By examining how a key antecedent of turnover intention operates within an organizational self-interest ethical climate, this paper advances our understanding of this complex phenomenon. A discussion of the study's limitations and suggestions for future research conclude the paper.
Keywords: 650; emotional exhaustion; ethical leadership; moderated mediation; self-interest ethical climate; turnover intention